Development of Integrated Tourism Information System PT. Yoy Manajemen Internasional - Nurzaman, Fahrul; Budilaksono, Sularso; Rosadi, Ahmad; Dewi , Euis Puspita; Febrianty, Febrianty (Sinkron : jurnal dan penelitian teknik informatika, 2021)
Yoy Manajemen Internasional is engaged in the tourism services sector. This company is a sharia-based hotel development and management company that was newly formed in October 2020. The hotel and tourism business network initially used a manual system. The tourism information system connects various entities at once, namely: hotel managers, tourist attraction operators, car rentals, restaurants, micro-enterprises supporting the tourism sector and tourists. Tourists can come from domestic or from abroad. The purpose of this research is to develop a tourism information system specifically for the sharia-based hotel industry that integrates all partners from PT Yoy Manajemen Internasional. This information system connects two interests, namely PMS (Property Management System) for the hospitality industry and YPA (YoY Personal Assistant) for mobile applications used by tourists. The system development method by applying the SDLC (System Development Life Cycle) method, consists of: planning, analysis, design, implementation, testing and training. Development of information systems with a management-to-consumer (top-down) and management-to-consumer (bottom-up) approach so that the development of information systems is expected to be more optimal. Testing this application was carried out through usability testing on both companies and SMEs assisted by PT. Yoy Management with a total of 50 respondents and 20 students of the Informatics study program. Usability testing using User-Interface and User-Experience users.